The Effect of Leadership Support, Organizational Culture, and Infrastructure on Student Achievement at the Tobelo Special School - Lily Amaliyah Sari Hi. A Mutalib; Abdul Rahman Jannang; Marwan Man Soleman (Jurnal Manajemen Bisnis, 2023)
This study aims to determine the effect of leadership support, organizational culture, and infrastructure on student achievement at SLB Negeri Tobelo school. The total population is 80 students and the sample in this study is 40 respondents. Data was collected by distributing questionnaires to all respondents. The analytical technique used in this research is multiple linear regression with SPSS 16.0 application. From the results of hypothesis testing, it was found that leadership support has a positive and significant effect on student achievement, organizational culture has a positive and significant effect on student achievement, and infrastructure has a positive and significant effect on student achievement.